(untitled) (Research, Society and Development, 2022)
The objective of the present study was to identify the physical and anthropometric characteristics of the athletes and their relationship with the practice of this sport. For this, we used the narrative literature review as a method. For Ferreira et al. (2018), the narrative review consists of a data collection carried out from secondary sources, through bibliographical research and aided in the experience lived by the authors. The research carried out was electronic, with articles from the VHL, which were available for download and in Portuguese. The main descriptors used are: anthropometry, soccer and performance. With the use of this strategy, a greater number of references were found, in addition to greater success in the search for published works according to the pre-established criteria. The articles researched on the subject are from 2012 to the present, excluding those that did not obtain connection and relevance with the topic addressed. And as a means of exclusion, studies that did not have substantiated information in which this research aims to review were removed. Thus, it was possible to conclude that physical and anthropometric characteristics such as height, weight, lean mass, fat mass, aerobic power and anaerobic power, are correlated with the physical performance of soccer players, both in the context of professional soccer and in analyzing in the context of youth soccer.